R2R-EU: Software for fragility fitting and evaluation of estimation uncertainty in seismic risk analysis. Issue 132 (May 2020) - Baraschino, Roberto; Baltzopoulos, Georgios; Iervolino, Iunio
Abstract: Analytical methods in performance-based earthquake engineering (PBEE) typically employ suites of ground motion records to run dynamic analysis of a structure's computer model. The sample size of ground motions used in this context, affects the estimation uncertainty that underlies the seismic risk metrics thus obtained. This article presents R2R-EU (record-to-record estimation uncertainty), which is a PBEE software tool that numerically implements various schemes for estimating structure-specific seismic fragility and for the quantification of the estimation uncertainty behind seismic risk estimates, emanating from record-to-record variability in structural response. The software accepts as input the results of structural dynamic analysis to a set of accelerograms and seismic hazard curves. Estimation uncertainty is quantified by providing statistics, such as mean and variance, of the estimators of the failure rate and the fragility parameters (where applicable) and possibly their distribution. The user can choose the analysis method among some resampling and/or simulation schemes belonging to the bootstrap family, the delta method and other solutions from probability and statistics theory. Highlights: Software tool for performance-based earthquake engineering research and applications. Structure-specific seismic fragility function fitting to the results of dynamic analysis. Incremental dynamic analysis, multi-stripe analysis and cloud analysis are supported. Risk metrics in the form of annual failure rates are obtained by integrating fragility with hazard. Estimation uncertainty behind fragility and risk estimates is inferred by various methods, including the bootstrap, the delta method and closed-form solutions.